(untitled) (Journal of the College of Education for Women, 2019)
The present study aimed to asspssment the nutrition a program to sample of student from internal departments of Baghdad University (AL-Jadiriya Complex) and the University of AL-MustanSiriya four grades and aged (19-24) year study included 150 male and female students by (75) male and (75) of female register height, weight nd body mass index were study habits and food pattern of the same sample (150) and by aspecial form and take the personal information interviews and record information on food intake during 24 hour .noted adifference practie in the weights and longths of male and female (sample).BMI rates were within the normal weight as the value of BMI for males aged (19- 21)and (22-24) and (22.21) and (23,37),respectively and that the highest percentage recorded by the body massindex (46,42%) within the normal weight males aged (19-24) and the the highest percentage recorded in the slim weight for males aged (22-24) reached (61,60,40%) for females and higher percentage recorded within the two categories slim (19-21)and (22-24) weight and was (57,57%)and (71,42%) respectively it is not an approach to longed in Arab countries .As with regard to food behavior there were so significant differences between males and females and the differences in favor of males has been observed where the highest percentage amounted to (77-33%)o f those who eat breakfast are permanent while recorded the highest rate of (36%)for those who consume wobbling (some time ).AS for the snack registered the highest percentage in favor of females who consume a permanent and (60%)And also noted that there were significant differences between males and females about food often( canned) and the differences in favor of females interms of percentage amounted to (46,66%)AS for miles reaching the percentage of (40%) and (33,33%) of the males excries is perm an ent and (44%)practice it is wobbling (some times) and for females reaching rtio (53,33%) dont excrise and(46,6640) practice it is wobbling (some times)As for the repetition of the types of food normalize it was noted that there were significant differences were in favor of males reaching the proportion who consume milk and dairy products from the male is permanent (30,67,40) while in females was (2040) as well as the case of vegetables ,but the differences were in favor of females in terms of percentage of(64%) of them eat vegetables are permanents while the figure was (40%) in males AS for fruits percentages were close reaching (96%) and (97%) in females respectively and (46%) of females’ eat sweets permanently while the percentage in males consume (60%) and sometimes wobbling as for soft drinks and weal’s has been taken up by the proportion at remakes decals reaching (26-66%) and (44%) repectively while the furnace when the percentage reached (42-67) and (53.33%)respectively as noted there were significant differences between the furnace and femles in the amountal mjor nutrients and energy as well as vitamins and minerals consumed as observed were differences in favor of males and generally evidenced by this study there is adecrease in the level of food culture in sample search for itrequires acorrection is throngs awareness and education foodKey Words :Evaluation , Food curriculum ,Weight , Length , Body Mass Index ( BMI) , Behavior and dietary babits Daily food in take.